Hv1 proton channels differentially regulate the pH of neutrophil and macrophage phagosomes by sustaining the production of phagosomal ROS that inhibit the delivery of vacuolar ATPases. Issue 5 (10th January 2014) - El Chemaly, Antoun; Nunes, Paula; Jimaja, Wedali; Castelbou, Cyril; Demaurex, Nicolas
Abstract : Hv1 channels sustain the rapid acidification of macrophage phagosomes, and maintain a neutral pH in neutrophil phagosomes. ABSTRACT: Production of ROS and maintenance of an appropriate pH within the lumen of neutrophil and macrophage phagosomes are important for an effective immune response. Hv1 proton channels sustain ROS production at the plasma membrane, but their role in phagosomes is not known. Here, we tested whether Hv1 channels regulate the pHp and sustain phagosomal ROS production in neutrophils and macrophages. The presence of Hv1 channels on phagosomes of human neutrophils and mouse macrophages was confirmed by Western blot and immunostaining. Phagosomal ROS production, measured with OxyBurst-coupled targets, was reduced in neutrophils and macrophages isolated from Hv1-deficient mice. Ratiometric imaging of FITC-coupled targets showed that phagosomes acidified more slowly in Hv1-deficient macrophages and transiently alkalinized when the V-ATPase was inhibited. In WT neutrophils, 97% of phagosomes remained neutral 30 min after particle ingestion, whereas 37% of Hv1-deficient phagosomes were alkaline (pH>8.3) and 14% acidic (pH<6.3). The subpopulation of acidic phagosomes was eliminated by V-ATPase inhibition, whereas NOX inhibition caused a rapid acidification, independently of Hv1 expression. Finally, V-ATPase accumulation on phagosomes was inversely correlated to intraphagosomal ROS production in neutrophils. These data indicate that Hvcn1 ablation deregulates neutrophil pHp, leading to alkalinization in phagosomes with residual ROS production or to the early accumulation of V-ATPase on phagosomes that fail to mount an oxidative response. Hv1 channels therefore differentially regulate the pHp in neutrophils and macrophages, sustaining rapid acidification in macrophage phagosomes and maintaining a neutral pH in neutrophil phagosomes.